2014
DOI: 10.25225/fozo.v63.i1.a1.2014
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of the mammals of Turkey and neighbouring regions: a review

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 195 publications
4
28
1
Order By: Relevance
“…Similarly, the Y chromosome differs from that of previous studies. The Y chromosome of the sample obtained from the Meryemana region of Trabzon is small acrocentric (Zima et al, 1998;Aslan and Zima, 2014). However, the Y chromosome obtained in the present study is large acrocentric in the karyotype set.…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, the Y chromosome differs from that of previous studies. The Y chromosome of the sample obtained from the Meryemana region of Trabzon is small acrocentric (Zima et al, 1998;Aslan and Zima, 2014). However, the Y chromosome obtained in the present study is large acrocentric in the karyotype set.…”
Section: Discussioncontrasting
confidence: 53%
“…2n=40 diploid set involving wholly acrocentric chromosomes is determined as a characteristic karyotype for Mus domesticus and Mus macedonicus in different parts of their distribution areas, although Robertsonian fusion leads to some karyological variations in this genus (Zima and Kral 1984;Gündüz et al 2000a, Arslan andZima 2014). Standard karyotype including 40 acrocentric chromosomes has been reported for M. domesticus and M. macedonicus from Central Anatolia, Western Black Sea and Eastern Anatolia in Turkey (Gündüz et al 2000b;Gözcelioğlu et al 2005;.…”
Section: Discussionmentioning
confidence: 99%
“…The karyotype characteristics were determined as 2n = 52, NFa = 94, and NF = 98, and the X and Y chromosomes were subtelocentric. Arslan and Zima (2014) stated that the karyotype characteristics of this species have not yet been reported from Turkey. In the N. anomalus karyotype, the number of diploid chromosomes is 2n = 52.…”
Section: Karyologymentioning
confidence: 99%
“…In the karyotype, 10 pairs of metacentric, 10 pairs of submetacentric, 2 pairs of subtelocentric, and 3 pairs of acrocentric chromosomes were usually recognized (Meylan, 1966;Rimsa et al, 1978;Zima, 1984). While the morphology of the X chromosome was reported as subtelocentric, submetacentric, and metacentric, the morphology of the Y chromosome was assessed as subtelocentric, submetacentric, and acrocentric (Fredga and Levan, 1969;Rimsa et al, 1978;Jimenez et al, 1984;Zima, 1984;Ivanitskaya, 1989;Arslan and Zima, 2014). Chassovnikarova et al (2009) reported C and NOR band characteristics of 3 males and 2 females collected from the Veleka River in the Stranca Mountains of Bulgaria.…”
Section: Karyologymentioning
confidence: 99%
See 1 more Smart Citation